Efficacy of high zinc biofortified wheat in improvement of micronutrient status, and prevention of morbidity among preschool children and women - a double masked, randomized, controlled trial - Sazawal, Sunil; Dhingra, Usha; Dhingra, Pratibha; Dutta, Arup; Deb, Saikat; Kumar, Jitendra; Devi, Prabhabati; Prakash, Ashish (Springer, 2018)
Biofortification of staple food crops with zinc (Zn) can be one of the cost-effective and sustainable strategies to combat zinc deficiency and prevent morbidity among the target population. Agronomic approaches such as application of Zn fertilizers to soil and/or foliar spray seem to be a practical tool for Zn biofortification of wheat. However, there is a need to evaluate its efficacy from randomized controlled trials. This study aimed to evaluate the efficacy of zinc biofortified wheat flour on zinc status and its impact on morbidity among children aged 4–6 years and non-pregnant non lactating woman of child bearing age (WCBA) in Delhi, India. In a community based, double-masked randomized controlled trial, 6005 participants (WCBA and child pairs) were enrolled and randomly allocated to receive either high zinc biofortified wheat flour (HZn, 30 ppm zinc daily) or low zinc biofortified wheat flour (LZn, 20 ppm zinc daily) for 6 months (WCBA @ 360 g/day and children @ 120 g/day). Baseline and endline blood samples were obtained for assessing hematological markers; zinc status and data on compliance and morbidity were collected. Compliance rates were high; ~ 88% of the WCBAs in both the groups consumed 50% or more of recommended amount of biofortfied wheat flour during the follow up. Similarly 86.9% children in HZn and 87.5% in LZn consumed 50% or more of recommended wheat flour intake. There was no significant difference in mean zinc levels between the groups at end study. This observation might be due to a marginal difference in zinc content (10 ppm) between the HZn and LZn wheat flour, and a short intervention period. However a positive impact of bio-fortification on self-reported morbidity was observed. Compared to children in LZn group, children in HZn group had 17% (95% CI: 6 to 31%, p = 0.05) and 40% (95% CI: 16 to 57%; p = 0.0019) reduction in days with pneumonia and vomiting respectively. WCBA in the HZn group also showed a statistically significant 9% fewer days with fever compared to LZn group. Biofortified wheat flour had a good compliance among children and WCBAs. Significant improvement on some of the self-reported morbidity indicators suggests that evaluating longer-term effects of biofortification with higher grain zinc content would be more appropriate. http://ctri.nic.in/Clinicaltrials/ , CTRI/2014/04/004527, Registered April 7, 2014.